Effectivity of Aloe vera bioactives as feed additive for broilers reared on deep litter - A.P Sinurat; T Purwadaria; T Pasaribu; W Rakhmani; J Dharma; J Rosida; S Sitompul; Udjianto . (Indonesian Center for Animal Research and Development (ICARD), 2004)
There are plenty of Indonesian plants contain usefull bioactive components. One of them is Aloe vera. Previous experiment showed that Aloe vera bioactives reduced aerob bacteria in the intestinal and improved feed efficiency in broilers reared in cages. The results however, gave some variations, may be due to variation in rearing the chickens. Two experiments were carried out to study the effectivity of Aloe vera bioactives as feed additives for broilers reared on deep litter. In the first study, six experimental diets in mash form were formulated, i.e.: Control (K); K + antibiotic; K + 0.50 g/kg dry Aloe vera (LBK); K + 1.00 g/kg LBK; K + anthraquinone; K + Aloe vera in semi-liquid form. The amount of semi liquid Aloe vera and the anthraquinone were equally to 1.00 g LBK/kg. Results showed that antibiotic improved body weight gain 6.10% and feed efficiency 5.50% better than the control, although statistically not significant (P>0.05). Aloe vera bioactives in low doses (0.50 g/kg) also improved weight gain (6.30%) and feed efficiency (5.20%) similar to the antibiotic. However, Aloe vera in high doses and anthraquinone (equal to 1.00 g/kg diet) did not improve performance of broilers. There were no significant changes on carcass yield, abdominal fat levels, weight of liver, gizard and gastro intestinal tract due to any feed additives tested. The second experiment were carried out to study the effectivity of feed additives when included in crumble diets. Six experimental diets, i.e.: Control (K), K + antibiotic, K + Semi-liquid Aloe vera (equal to 1.00g dry Aloe vera/kg), K + 0.50 g dry Aloe vera/kg, K + 1.00 g dry Aloe vera/kg, K + 0.50 g dry Aloe vera + 0.50 g Curcuma xanthorrhiza meal/kg. All diets were fed in crumble form. Results showed that chickens fed with feed additives (antibiotic or Aloe vera bioactives) have a significantly (P<0.05) higher body weight gain and feed efficiency than those fed with control diet. The best weight gain was achieved by low dose dry Aloe vera (1342 g/bird) and the lowest was the control (1039 g/bird). The best feed conversion ratio was achieved by antibiotic treatment (1.756) followed by low dose dry Aloe vera + curcuma meal (1.758) and the worst was showed by the control (1.908). It is concluded that Aloe vera bioactives at low dose (0.50 g/kg diet) could improve body weight gain and feed efficiency of broilers reared on deep litter. The improvement achieved was similar as the antibiotic. The bioactive is more effective when fed in crumble diets. Key words: Broilers, bioactives, Aloe vera